Spontaneous rupture of renal angiomyolipoma during pregnancy - Mariana Mouraz Lopes dos Santos; Sara Marques Soares Proença; Maria Inês Nunes Pereira de Almeida Reis; Rui Miguel Almeida Lopes Viana; Luísa Maria Bernardo Martins; João Manuel dos Reis Colaço; Filomena Maria Pinheiro Nunes (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2014)
Renal angiomyolipoma is a benign tumor, composed of adipocytes, smooth muscle cells and blood vessels. The association with pregnancy is rare and related with an increased risk of complications, including rupture with massive retroperitoneal hemorrhage. The follow-up is controversial because of the lack of known cases, but the priorities are: timely diagnosis in urgent cases and a conservative treatment when possible. The mode of delivery is not consensual and should be individualized to each case. We report a case of a pregnant woman with 18 weeks of gestation admitted in the emergency room with an acute right low back pain with no other symptoms. The diagnosis of rupture of renal angiomyolipoma was established by ultrasound and, due to hemodinamically stability, conservative treatment with imaging and clinical monitoring was chosen. At 35 weeks of gestation, it was performed elective cesarean section without complications for both mother and fetus.